The feasibility of crop diversification in rice based cropping systems in haor ecosystem - Shopan, J; Bhuiya, MSU; Kader, MA; Hasan, MK (Journal of the Bangladesh Agricultural University, 2013)
An experiment was conducted in five farmers field in Dingaputa haor of Purba Tetulia village, Mohangonj Upazila in Netrakona district during the period from 20 July 2010 to 15 May 2011. The objective of the study was to determine the feasibility of growing short duration vegetable and oil crops in seasonal fallow of Boro rice-Fallow-Fallow cropping patterns in terms of both combined yields and economic performance. Six short duration vegetables such as potato, red amaranth, stem amaranth, spinach, radish and mustard were the first crops and Boro rice (var. BRRI dhan28) was the second crop. Thus there were six types of cropping patterns Potato-Boro rice- Seasonal flood, Red amaranth-Boro rice- Seasonal flood, Stem amaranth-Boro rice- Seasonal flood, Spinach-Boro rice- Seasonal flood, Radish-Boro rice- Seasonal flood and Musturd-Boro rice- Seasonal flood. The agronomic productivity (rice equivalent yield t ha-1) of the cropping patterns Potato-Boro rice- Seasonal flood, Red amaranth-Boro rice- Seasonal flood, Stem amarnth-Boro rice- Seasonal flood, Spinach-Boro rice- Seasonal flood, Radish-Boro rice- Seasonal flood and Mustard-Boro rice- Seasonal flood were 22.42, 15.47, 17.04, 17.79, 22.11 and 11.56 t ha-1, respectively with economic productivity (gross return Tk ha-1) of 364162.50, 251712.50, 276900.00, 292012.50, 359125.00 and 187850.00, respectively and the benefit cost ratio of 1.88, 1.52, 1.65, 1.69, 1.75 and 1.12, respectively From diversification practices in Dingaputa haor ecosystem Potato-Boro rice- Seasonal flood and Radish-Boro rice- Seasonal flood cropping patterns were found to be the most dominant cropping patterns in economic terms. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14697 J. Bangladesh Agril. Univ. 10(2): 211-216, 2012